Pengaruh Penggunaan QField for QGIS dengan Model Team Assisted Individualization terhadap Kreativitas dan Hasil Belajar Siswa pada Materi Dasar-Dasar Pemetaan di SMAN 6 Solok Selatan - Azzahra, Sukma; Mariya, Sri (YASIN, 2025)
The limited implementation of mobile-based geospatial technology in Geography education forms the background of this study, despite its significant potential to enhance students' creativity and learning outcomes. This research aims to (1) analyze the effect of using QField for QGIS integrated with the Team Assisted Individualization (TAI) model on students' creativity, and (2) describe its impact on learning outcomes in the topic of basic mapping at SMAN 6 Solok Selatan. A quantitative approach was used with a quasi-experimental design. The sample was selected through purposive sampling, involving two classes—E2 as the experimental group and E4 as the control group. Data were collected through tests, questionnaires, observations, and documentation, and analyzed using normality and homogeneity tests, t-tests, and N-Gain calculations. The results indicate that integrating QField for QGIS with the TAI model significantly improves students' creativity (p < 0.05), shifting from the "moderately creative" to the "creative" category. N-Gain analysis shows an average learning outcome increase of 0.71 (high category) in the experimental class and 0.51 (moderate category) in the control class. The study concludes that integrating mobile-based geospatial applications with cooperative learning models is effective in enhancing students' creativity and academic performance in basic mapping materials. The findings support the implementation of adaptive technological innovations in Geography education in response to digital advancements.